2015
DOI: 10.1371/journal.ppat.1005019
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Genome Recognition Induced Acetylation of Nuclear IFI16 Is Essential for Its Cytoplasmic Translocation, Inflammasome and IFN-β Responses

Abstract: The IL-1β and type I interferon-β (IFN-β) molecules are important inflammatory cytokines elicited by the eukaryotic host as innate immune responses against invading pathogens and danger signals. Recently, a predominantly nuclear gamma-interferon-inducible protein 16 (IFI16) involved in transcriptional regulation has emerged as an innate DNA sensor which induced IL-1β and IFN-β production through inflammasome and STING activation, respectively. Herpesvirus (KSHV, EBV, and HSV-1) episomal dsDNA genome recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
122
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 33 publications
7
122
0
Order By: Relevance
“…NOD2-deficient mice had enhanced susceptibility to infection with respiratory syncytial virus (RSV), decreased IRF3 phosphorylation, and type I IFN production. Redundancy of innate immune response pathways to herpesviruses is well known, and some of the recently described pattern recognition receptors, such as IFI16 and cGMP-AMP synthase (cGAS), appear to be broad sensors of different herpesviruses (29,(36)(37)(38)(39)(40)(41). In the case of NOD1, specific HCMV suppression through NOD1 activation (but not HSV-1 suppression) suggests the possible use of specialized pathways through HCMV which could be targeted for virus control.…”
Section: Discussionmentioning
confidence: 99%
“…NOD2-deficient mice had enhanced susceptibility to infection with respiratory syncytial virus (RSV), decreased IRF3 phosphorylation, and type I IFN production. Redundancy of innate immune response pathways to herpesviruses is well known, and some of the recently described pattern recognition receptors, such as IFI16 and cGMP-AMP synthase (cGAS), appear to be broad sensors of different herpesviruses (29,(36)(37)(38)(39)(40)(41). In the case of NOD1, specific HCMV suppression through NOD1 activation (but not HSV-1 suppression) suggests the possible use of specialized pathways through HCMV which could be targeted for virus control.…”
Section: Discussionmentioning
confidence: 99%
“…Proximity ligation assay (PLA) was performed using the Duolink in situ detection kit (Sigma) as per the manufacturer's instructions (33,34). Briefly, uninfected and infected cells were fixed with 4% paraformaldehyde solution for 15 min, permeabilized with Triton X-100 for 5 min, washed with phosphate-buffered saline (PBS), and incubated for 1 h with the Duolink blocking buffer.…”
Section: Cells and Virusmentioning
confidence: 99%
“…IFI16 is a multifunctional DNA binding protein and has been implicated in various cellular functions such as transcriptional regulation, apoptosis, autoimmunity, and cell cycle regulation (25)(26)(27). Studies by us and others have reported the role of IFI16 as a DNA sensor that detects nuclear replicating herpesviral genomes such as KSHV, herpes simplex virus 1 (HSV-1), EpsteinBarr virus (EBV), and bovine herpesvirus 1 (BoHV-1), leading to IFI16 -apoptosis-associated speck-like protein containing a CARD (ASC)-procaspase-1 inflammasome formation that results in the production of the inflammatory cytokine interleukin 1␤ (IL-1␤) (28)(29)(30)(31)(32)(33). We have also shown that IFI16-mediated inflammasomes are activated during prolonged KSHV latency in endothelial and B cells, leading to a constitutive state of IL-1␤ activation (34).…”
mentioning
confidence: 99%
“…We have also shown that IFI16-mediated inflammasomes are activated during prolonged KSHV latency in endothelial and B cells, leading to a constitutive state of IL-1␤ activation (34). Recently, IFI16 was also shown to be involved in the induction of IFN-␤ during KSHV and HSV-1 de novo infection of target cells via the IFI16 -stimulator of interferon genes protein (STING)-TANK-binding kinase 1 (TBK)-interferon regulatory factor 3 (IRF3) axis (31,32,35,36).…”
mentioning
confidence: 99%